Feed Intake, Blood Parameters, Digestibility and Live Weight Gain of Male Bali Cattle (Bos javanicus) Fed Ammoniation Rice Straw Supplemented by Waru (Hibiscus tiliaceus) Flower Extracts - Sri Rahayu; Veven Raymexen Bonat; Muhamad Bata (ANIMAL PRODUCTION, 2021)
The objective of this study was to evaluate the effect of Hibiscus tiliaceus flower extracts supplementation in concentrate on performance, nutrient digestibility and blood metabolites of Bali cattle. Sixty of male Bali cattle averaging 225 ± 09.15 kg initial body weight were used in this study. They were divided into two groups. The first group (as control) was cattle fed ammoniated rice straw and concentrate (R1) and the second group was fed as the same as the control group, but concentrate was supplemented with H. tiliaceus flower extract at 200 ppm/kg of dry matter (R2). Variables measured were dry matter digestibility (DMD), organic matter digestibility (OMD), neutral detergent fiber digestibility (NDFD), and acid detergent fiber (ADFD) using total collection method. Other variables were blood glucose and urea, average daily gain (ADG), feed conversion (FC) dan feed efficiency (FE). T-test showed that DMD, OMD, ADFD, and NDFD in the second group (R2) were higher (P<0.05) than control (R1). However, there was no significant difference (P>0.05) between performance (ADG, FC, FE) and blood parameters of urea and glucose between the groups fed diets supplemented with H. tiliaceus flower extracts and control group. There was an increase in ADG and FE on R2 (0.63 ± 0.23 kg and FE 5.54 ± 1.89) compared to R1 (0.54 ± 0.32 kg and 0.54 ± 0.32). The study concluded that supplementation of Hibiscus tiliaceus flower extracts as feed additive in the concentrate diet can increase nutrient digestibility and tend to improve the performance of Bali cattle.